2018
DOI: 10.1136/bmjopen-2017-021467
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing training of community health workers in low-income and middle-income countries: a systematic scoping review of the literature

Abstract: ObjectivesUnderstanding the current landscape of ongoing training for community health workers (CHWs) in low-income and middle-income countries (LMICs) is important both for organisations responsible for their training, as well as researchers and policy makers. This scoping review explores this under-researched area by mapping the current delivery implementation and evaluation of ongoing training provision for CHWs in LMICs.DesignSystematic scoping review.Data sourcesMEDLINE, Embase, AMED, Global Health, Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 75 publications
5
90
0
Order By: Relevance
“…In addition to supportive supervision, training of CHWs before the commencement of their duties and other in-service training is seen as particularly useful in enhancing their knowledge and skills for service provision. Training as an indispensable tool in the work of community health workers is useful in the transfer of useful skills and information for the effective delivery of health services to hard-to-reach populations 44,45 . CHWs, therefore, consider training as an essential component in achieving their mandate as health workers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to supportive supervision, training of CHWs before the commencement of their duties and other in-service training is seen as particularly useful in enhancing their knowledge and skills for service provision. Training as an indispensable tool in the work of community health workers is useful in the transfer of useful skills and information for the effective delivery of health services to hard-to-reach populations 44,45 . CHWs, therefore, consider training as an essential component in achieving their mandate as health workers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these encouraging results, future studies that explore the sustainability of these bolstering mechanisms after the intervention has been established will help evaluate the long-term effectiveness of the intervention. If CHWs need to receive repeated trainings to ensure effectiveness, modalities of this must be factored into interventions that rely mostly on CHWs [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, knowledge is likely to decrease further by 50% or more in the next ve years without any further ongoing training or education [16]. A review of ongoing trainings for CHWs from different LMICs on different health topics have shown positive results for knowledge retention following refresher trainings [17]. A study on refresher training for CHWs in India suggested the knowledge retained among CHWs following the refresher training at 1-year post-intervention was higher than the knowledge retained 2 months after the initial training [18].…”
Section: Discussionmentioning
confidence: 99%